IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS REWARD AND PUNISHMENT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X IPA DI SMA ISLAM AL-HIKMAH TAJINAN MALANG - Wildaninaila Wildaninaila; Nur Hasan; Moh. Eko Nasrullah (VICRATINA, 2022)
This study aims to determine: 1. How the implementation of islamic religious education learning based on reward and punishment to increase student motivation in Islamic High School Al Hikmah Tajinan 2. The result of the implementation of islamic religious education learning based on reward and punishment to increase student motivation in Islamic High School Al Hikmah Tajinan.  The research method that used in this research is Classroom Action Research(CAR). In collecting data, Researchers used qualitative research method, namely conducting observations, documentations, and tests. The results of the research show that The implementation of reward and punishment at SMA Islam Al-Hikmah Tajinan carried out by  Teachers and researchers. They give the reward to the students who get the high score, the reward is in the form of verbal and non verbal praise. While for the punishment, they give preventive and repressive punishment. This research is expected to be useful for teachers and parents to be more enthusiastic about motivating students to be more active in learning.